EVALUASI KONDISI SISTEM PENYALIRAN AKTUAL UNTUK MEMBUAT PERENCANAAN SISTEM PENYALIRAN DI PIT B RAWA SELATAN TAMBANG BATUBARA PT. MANDALA KARYA PRIMA JOB SITE PT. MANDIRI INTIPERKASA, KALIMANTAN UTARA - Febrian Febrian; Murad Murad (Journals Mining Engineering : Bina Tambang, 2019)
Abstract.PT. Mandala Karya Prima (MKP) is a mining contractor who undertake mining activities in Pit B Rawa Selatan, District and Sub-District Sembakung Sesayap Hilir, Nunukan and Tana Tidung, North Kalimantan Province. Based on the analysis of rainfall data in 2008-2017, the planned rainfall was 95,403 mm / day. Research location, Pit B South Rawa PT. MKP, the actual condition in 2018 has 2 catchment areas with different areas, there is peat runoff water with a discharge of 184.000 m3 / hour, there are 2 sumps namely temporary sump A5 and main sump A2. Recommended temporary dimensions of A5 sump with a maximum volume of 416.520 m3, elevation control on main sump with +16 water elevation, making an open channel in the North A5 Inpit Dump area. In 2019 the authors planned 4 catchment areas with different areas, there were 3 sumps, namely temporary sump A5, temporary sump A6 and main sump A2. The author plans elevation control with a water elevation of +16 in 2019 in the main sump A2 area, making 2 open channels namely in the higwall and lowwall mine areas. The pumping system was carried out using HDPE pipes and 10 pumps unit merk Multiflo 420 EXHV. Settling pond planned for 4 compartments with a capacity of each compartment of 1422,53 m3.Keywords: Rainfall, Catchment Area, Sump, Open Channel, Settling Pond